Optimization and Control for Solid Oxide Fuel Cell System Hybrid DC Microgrids From the Perspective of High Efficiency, Thermal Safety, and Transient Response - Zhang, Lin; Tang, Wenhui; Wang, Feng; Xie, Chao; Zhou, Weibin; Xie, Hongtu (Frontiers in Energy Research, 2022)
Managing the power transients with both high efficiency and thermal management constraints is a difficult task in the solid oxide fuel cell (SOFC) hybrid direct-current (DC) microgrids. This paper proposed a SOFC-based DC microgrid, which consists of the SOFC standalone system, DC microgrid network, DC/DC boost converter, along with the associated DC/DC load. The control and optimization strategy of the SOFC-based DC microgrids has been designed, including the thermal and electrical characteristics analysis. First, the voltage and current regulator based on the proportional-integral (PI) is designed, which can maintain the voltage stability of the proposed SOFC system. Besides, the optimal regulator based on the optimal operating points (OOPs) is designed, which can realize the high efficiency and steady-state thermal safety of the proposed SOFC system. Finally, the main performance, including the SOFC stack electrical characteristics verification, SOFC stand-alone system electrical and thermal response, load tracking characteristics, and system efficiency are observed and discussed in the proposed control and optimization strategy. Experimental results verify the correctness of the theoretical analysis and the effectiveness of the proposed optimization and control strategy.